GWAS in myopia: insights into disease and implications for the clinic. (3rd March 2016) - Williams, Katie M; Hammond, Christopher J
ABSTRACT: Myopia is the most common eye trait worldwide and the prevalence is increasing. It is known to be highly heritable; total genetic variation explains up to 70–80% of variance. In an attempt to better understand the genetic architecture of myopia, with an ultimate view to better predict genetic risk and develop targeted treatments, several genome-wide association studies have been performed in the last 6 years. In this review we focus on what a genome-wide association study involves, what studies have been performed in relation to myopia to date, and what they ultimately tell us about myopia variance and functional pathways leading to pathogenesis. The current limitations of genome-wide association studies are reviewed and potential means to improve our understanding of the genetic factors for myopia are described.